Strategi Pemasaran Rumah Makan Bu Yati di Kota Bengkulu Pada Masa Pandemi Covid-19 - Asep Kikin Mutakin; Ahmad Soleh; Ida ayu Made Er Meytha Gayatri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine how the strategy of Rumah Makan Bu Yati in Bengkulu City during the COVID-19 pandemic and identify the strengths, weaknesses, opportunities and threats faced by Rumah Makan Bu Yati and determine a suitable strategy to be applied to adapt in the new normal. In the long term, the results of this study are expected to contribute to the development of marketing strategies to deal with emergency and uncertain situations. This study uses the SWOT analysis method by selecting consumers who come as respondents. the research sample consisted of internal factors, namely 7 people who were the Owners and Employees of Rumah Makan Bu Yati and external factors as many as 35 people who were consumers who came to Rumah Makan Bu Yati. Based on the SWOT analysis, it is known that Rumah Makan Bu Yati has a strength value of 30.58 and a weakness of 13.99 so that the complement of IFAS is 30.58–13.99 = 16.59, while the opportunity value is 17.14 and the threat is 12.22 so that the EFAS quadrant is 17, 14 – 12.22 = 4.92 so it can be seen that Rumah Makan Bu Yati is at coordinates (16.59: 4.92) in quadrant (1). This quadrant position is a very profitable position, a field that has opportunities and opportunities therefore they can take full advantage of existing opportunities. Thus, Rumah Makan Bu Yati is expected to implement a strategy that supports an aggressive growth policy.